Studi Korelasi Model Pembelajaran Auditory, Intellectually, And Repetition (Air) Terhadap Gaya Belajar Siswa Pada Mata Pelajaran PAI Di Kelas XI SMA Negeri 1 Selomerto Wonosobo - Isnaeni Ma’rifah; Ahmad Khoiri; Siti Lailliyah (JOURNAL SAINS STUDENT RESEARCH, 2025)
21st-century education demands students to master communication, collaboration, critical thinking, and creativity. However, Islamic Religious Education (PAI) learning in schools is still largely dominated by traditional lecture methods that fail to accommodate students’ diverse learning styles. This study aims to examine the influence of the Auditory, Intellectually, and Repetition (AIR) learning model on students’ learning styles in PAI at SMA Negeri 1 Selomerto. The research employed a quasi-experimental method involving two groups: the experimental class using the AIR model and the control class using the lecture method. Data were collected through tests and questionnaires, and analyzed using the Mann-Whitney U test and Pearson correlation. This study found that the AIR model had a positive and significant effect on students' learning styles (U = 338.000, Z = -2.180, and p = 0.029). The learning style scores in the experimental class were higher than those in the control class, and there was a very strong correlation between the implementation of the AIR model and students' learning styles, with a Pearson correlation coefficient of r = 0.989 (p < 0.001). Thus, the AIR model is effective in enhancing students' learning styles in Islamic Religious Education (PAI), making the learning process more adaptive and meaningful.